(untitled) (Journal of Partial Differential Equations, 2022)
The aim of this paper is to study the obstacle problem associated with an elliptic operator having degenerate coercivity, and L^1-data. The functional setting involves Lebesgue-Sobolev spaces with variable exponents. We prove the existence of an entropy solution and show its continuous dependence on the L^1-data in W^1,q(·)(Ω) with some q(·)>1.